2012
DOI: 10.1186/1471-2458-12-104
|View full text |Cite
|
Sign up to set email alerts
|

Stability and change in screen-based sedentary behaviours and associated factors among Norwegian children in the transition between childhood and adolescence

Abstract: BackgroundIn order to inform interventions to prevent sedentariness, more longitudinal studies are needed focusing on stability and change over time in multiple sedentary behaviours. This paper investigates patterns of stability and change in TV/DVD use, computer/electronic game use and total screen time (TST) and factors associated with these patterns among Norwegian children in the transition between childhood and adolescence.MethodsThe baseline of this longitudinal study took place in September 2007 and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 44 publications
(70 reference statements)
4
54
1
5
Order By: Relevance
“…However, no association between maternal education and 3-year change in sedentary time was observed in Australian children (age 10–12 years at baseline) [39] and change in children’s screen-based sedentary behaviour may be inversely associated with parental education. [41], [42] Currently, the socioeconomic patterning of change in sedentary behaviour during childhood remains unclear; however, it appears that the association may vary dependent upon how these constructs are defined and measured. That said, in sensitivity analyses, the direction of the association between SES and change in sedentary time remained unchanged in models using parents educational attainment and each of our component markers of SES individually (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, no association between maternal education and 3-year change in sedentary time was observed in Australian children (age 10–12 years at baseline) [39] and change in children’s screen-based sedentary behaviour may be inversely associated with parental education. [41], [42] Currently, the socioeconomic patterning of change in sedentary behaviour during childhood remains unclear; however, it appears that the association may vary dependent upon how these constructs are defined and measured. That said, in sensitivity analyses, the direction of the association between SES and change in sedentary time remained unchanged in models using parents educational attainment and each of our component markers of SES individually (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In the HEalth In Adolescents (HEIA) cohort study it has previously been reported that time spent on television and video viewing (TV/DVD) and on computer and electronic games (PC/games) increased significantly among boys and girls from the age of 11 to 13 years [35]. Demographic factors related to adolescents’ total screen time between the ages 11 to 13 years were lower parental education among girls and not living in two-parent families among boys [35].…”
Section: Introductionmentioning
confidence: 99%
“…Demographic factors related to adolescents’ total screen time between the ages 11 to 13 years were lower parental education among girls and not living in two-parent families among boys [35]. Determinants in the home environment may be important target variables to consider in interventions aiming to reduce adolescents’ prospective screen time, and thus explain some of the educational differences in adolescents screen time.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported a consistent amount of the total time spent sitting in front of a television or a computer, and they reveal that the time spent watching television was replaced by time spent using a computer (28,29). Other studies found an increase in the time spent sitting in front of a television or computer (30)(31)(32). Further analyses that use the same methodology in different countries are needed to facilitate sound comparisons between countries.…”
Section: Introductionmentioning
confidence: 99%